Wanderings in the Orient - Reese, A. M. (Albert Moore), 1872-1965 (Salt Lake City, UT : Project Gutenberg, 2008)
"Wanderings in the Orient" by A. M. Reese is a travel narrative written in the early 20th century, specifically around 1919. This book offers a firsthand account of various experiences and observations as the author journeys through regions such as the Philippines, Singapore, and other parts of Southeast Asia. The likely topic revolves around the cultural and social dynamics of these places, depicting the life, landscapes, and people encountered during the travels. The book is structured as a series of sketches or vignettes based on Reese's explorations, often focusing on specific locations and their unique characteristics. Each chapter highlights different aspects of life in the orient, from the simplicity of village life in the Philippine barrio of Mariveles to the historical significance of the leper colony at Culion. Reese also captures the vibrant scene of Singapore as a melting pot of cultures and delves into the bustling life of modern Manila. Through rich descriptions and vivid illustrations, the reader is invited into the diverse tapestry of the East, examining both the beauty and challenges faced by the inhabitants as well as the author$1 (Bs reflections on their way of life. (This is an automatically generated summary.)s
Release date is 2008-09-26
Keywords: East Asia -- Description and travel